Quality of life of nursing internship students in Saudi Arabia during the COVID-19 pandemic: A cross-sectional study - Rizal Angelo N. Grande; Vincent Edward R. Butcon; Maria Charito Laarni Indonto; Liza Mendizabal Villacorte; Daniel Joseph E. Berdida (Elsevier, 2021)
Background: The COVID-19 pandemic caused an unprecedented negative impact on the usual way of life. The fight against this fatal virus demands the united force of healthcare workers, including nurse interns (NIs). Therefore, being unprepared for a crisis of this magnitude which never happened in a century, nurses and NIs experience stress, trauma, and mental health issues that affect their quality of life (QoL). Objectives: This study inquired the demographic of the NIs, the responses of the participants to the domains of Quality of Life Evaluation Scale (QOLES), and the relationship between the participants' responses to the scale to each of their demographic profiles. Methods: This study used a quantitative cross-sectional design through an electronic survey form in the collection of data. Utilizing total enumeration as sampling technique, 152 NIs in Saudi Arabia completed the survey. Results: Across the 22-item questionnaire, the NIs still feel safe being in the hospital, clinic, or other healthcare facilities with a mean of 3.32; while item 8, which is having abundant energy, had the lowest mean of 1.91. The overall mean is 2.61, interpreted as 'important,' signifying that the participants 'agree to some extent.' Conclusion: The QoL of the NIs focused more on their psychological wellbeing and social relationships while the environmental and physical domains had lesser emphasis. In terms of enhancing specificity, comprehensiveness, and generalizability of future studies in QoL, a larger sample and more rigorous design is recommended.